Evaluation of the FAS and FASL Gene changes in women with premature ovarian failure: A case-control study - Zhima Akhavansales; Alimohammad Mosadeghmehrjardi; Hamid Reza Ashrafzadeh; Shadnaz Fakhteh Yavari; Mohammad Taher Tahoori; Morteza Bitaraf Sani; Mahnaz Mohammadi; Fateme Montazeri; Nasrin Ghasemi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Premature ovarian failure (POF), is menopause occurring before the age of 40, affecting 1-3% of women worldwide. The risk of POF increases with altered immunological parameters such as FAS and FASL genes, which play a fundamental role in embryogenesis and cellular homeostasis. Objective: The study aimed to investigate the potential role of FAS and FASL genes in POF pathogenesis. Materials and Methods: In this case-control study, the polymorphisms of FAS-670A/G and FASLIVS2nt_124A/G apoptotic genes were analyzed in 51 Iranian women suffering from POF, and 61 healthy controls. Isolation of DNA was done using the salting-out method, and genotypic analysis was performed for all the subjects using the polymerase chain reaction-restriction fragment length polymorphism method. Results: Our results revealed that homozygous FAS-670A/A and G/G, and heterozygous FAS-670A/G are not significantly different between cases and controls (p = 0.99). Also, in different genotyping models of FASIVS2nt_124, polymorphisms were not related to POF risk (p = 0.23). Conclusion: There is no statistical association between these polymorphisms and POF risk in women referred to genetic counseling clinics.